Transcriptional and epigenetic modulation of autophagy promotes EBV oncoprotein EBNA3C induced B-cell survival - Bhattacharjee, Shaoni (Cell Death Dis, 2018)
Epstein-Barr virus (EBV) oncoprotein EBNA3C is indispensable for primary B-cell transformation and maintenance of lymphoblastoid cells outgrowth. EBNA3C usurps two putative cellular pathways—cell-cycle and apoptosis, essentially through modulating ubiquitin-mediated protein-degradation or gene transcription. In cancer cells, these two pathways are interconnected with autophagy,—a survival-promoting catabolic network in which cytoplasmic material including mis/un-folded protein aggregates and damaged organelles along with intracellular pathogens are degraded and recycled in lysosomal compartments. Studies have shown that tumor viruses including EBV can manipulate autophagy as a survival strategy. Here, we demonstrate that EBNA3C elevates autophagy, which serves as a prerequisite for apoptotic inhibition and maintenance of cell growth. Using PCR based micro-array we show that EBNA3C globally accelerates autophagy gene transcription under growth limiting conditions. Reanalyzing the ENCODE ChIP-sequencing data (GSE52632 and GSE26386) followed by ChIP-PCR demonstrate that EBNA3C recruits several histone activation epigenetic marks (H3K4me1, H3K4me3, H3K9ac, and H3K27ac) for transcriptional activation of autophagy genes, notably ATG3, ATG5, and ATG7 responsible for autophagosome formation. Moreover, under growth limiting conditions EBNA3C further stimulates the autophagic response through upregulation of a number of tumor suppressor genes, notably cyclin-dependent kinase inhibitors—CDKN1B (p27(Kip1)) and CDKN2A (p16(INK4a)) and autophagy mediated cell-death modulators—DRAM1 and DAPK1. Together our data highlight a new role of an essential EBV oncoprotein in regulating autophagy cascade as a survival mechanism and offer novel-targets for potential therapeutic expansion against EBV induced B-cell lymphomas.